Thermal compression analysis of adsorption bed for cooling applications - Quek, Johan Yi Xiang (2017)
This report presents the study of adsorption bed performance of an adsorption chiller based on the adsorption-desorption cycle. Hence, we have calculated the volumetric efficiency of an adsorption bed for six commercially available adsorbents such as type A, RD, 3A silica gel, CaCl2-in-silical gel, AQSOA types Z01 and Z02 zeolites with water as the adsorbate. The adsorption cooling is generated at the evaporator by the unique union of the adsorption-triggered-evaporation and desorption-activated-condensation. Based on the individual properties of each adsorbent, the performances such as temperature, pressure, and uptake were obtained using MATLAB for cycles for 1760 s, 1920 s and individually optimised cycles. Isotherms of each adsorbent were calculated and plotted for temperatures 30°C, 40°C, 50°C, 60°C, 70°C ,80°C for uptake at varying pressures which would be compared against results from simulated results for volumetric efficiency. From the volumetric efficiency, the packing density of each material was obtained which would tell about the amount of void volume of the adsorbents. The void volume would affect the amount of adsorbates flowing through the system which in turn would affect the overall cooling performance of the adsorption chiller. Kinetics for each adsorbate were also plotted for better understanding of the rate of adsorption. It was found that the kinetics of adsorbents affects the performance of the adsorbents with Type 3A having the best packing density for all cycles and CaCl¬2 -in -silica gel water has the greatest potential for improvement.